Strange yet Familiar Sounds in Zosha Di Castri’s String Quartet No. 1 - Morrison, Landon (Circuit, 2018)
This paper presents a detailed analysis of Zosha Di Castri’s String Quartet No. 1 (2016), situating the work in relation to the composer’s still-nascent oeuvre and showing how it contains a diverse mix of stylistic impulses within its relatively compact form. The concept of defamiliarization, borrowed from literary criticism, provides a useful theoretical basis for understanding the work. By presenting familiar musical figures within strange new contexts, Di Castri effectively bypasses habitual modes of reception and encourages the listener to engage more actively with the work’s multi-coded discourse. This revivification of perceptual awareness is accomplished using a number of compositional techniques, including the juxtaposition or superimposition of contrasting materials, the transformation of motives, and the distortion of formal syntax. Taken together, these defamiliarizing devices mount an aesthetic intervention that playfully subverts compositional norms, allowing Di Castri to take a decisive step forward in the development of her own musical style.